The Novel Coronavirus, Handwashing and Coconut Oil - Dayrit, Fabian M (Archīum Ateneo, 2020)
Speaker: Dr. Fabian M. Dayrit Academician, National Academy of Science and Technology President, Integrated Chemists of the Philippines Professor Emeritus, Ateneo de Manila University -- On Dec. 31, 2019, China informed the WHO of cases of pneumonia of unknown cause in Wuhan City and Jan 11, 2020, Chinese state media reported the first known death from this novel coronavirus. Meanwhile, numerous unverified videos were uploaded on the internet showing many deaths from this new disease, which was initially called 2019-nCoV. On Jan. 30, WHO declared the 2019-nCoV outbreak a "public health emergency of international concern.“ On this same day, Dr. Mary Newport and I posted our first article on social media where we wrote: “Given the considerable scientific evidence for the antiviral activity of coconut oil, lauric acid and its derivatives and their general safety, and the absence of a cure for 2019-nCoV, we urge that clinical studies be conducted among patients who have been infected with 2019-nCoV. This treatment is affordable and virtually risk-free, and the potential benefits are enormous.” In the webinar, Dr. Dayrit will briefly explained the basis for this proposal. Three antiviral mechanisms were proposed which were based on studies done on metabolites from coconut oil which are formed upon ingestion, such as monolaurin and lauric acid. The first mechanism was discussed: the disruption of the viral membrane. Although VCO and its metabolites are already established antivirals, its efficacy against SARS-CoV-2 still needs to be proven and the effective dose needs to be established. If frequent handwashing is an effective defense against this virus, perhaps taking VCO in sufficient amounts may be just as effective. However, as we learn more about COVID-19, it is becoming apparent that this virus can attack numerous organs in the body. So, we will likely need to do many things to protect ourselves from this virus.